Studies on the role of IS1216E in the formation and dissemination of poxtA-carrying plasmids in an Enterococcus faecium clade A1 isolate. (8th August 2020) - Shan, Xinxin; Li, Xin-Sheng; Wang, Nannan; Schwarz, Stefan; Zhang, Su-Mei; Li, Dexi; Du, Xiang-Dang
Abstract: Objectives: To analyse the role of IS 1216E in the dissemination of the phenicol-oxazolidinone-tetracycline resistance gene poxtA in an Enterococcus faecium clade A1 isolate. Methods: MICs were determined by broth microdilution. The poxtA -positive isolate was typed by MLST. The two plasmids were characterized by PCR, conjugation, S1-PFGE, Southern blot hybridization and WGS analysis. The presence of translocatable units (TUs) was examined by PCR and sequencing. Results: Isolate E1077 contains the 217661 bp conjugative plasmid pE1077-217 and the 23710 bp mobilizable plasmid pE1077-23. pE1077-217 harbours erm (B), aac (A)- aph (D), aadE, spw, lsa (E), lnu (B), aphA3 and dfrG, whereas pE1077-23 carries a Tn 6657 -like transposon containing poxtA and fexB . pE1077-23 was apparently formed by an IS 1216E -mediated composite transposon–plasmid fusion event, involving a replicative transposition process. Conjugation experiments showed that pE1077-23 is mobilizable by pE1077-217. Moreover, a novel 31742 bp plasmid, pT-E1077-31, was found in a transconjugant. WGS analysis indicated that pT-E1077-31 was formed by the integration of a Tn 6657 -derived, IS 1216E -based translocatable unit, which carried fexB and poxtA, into a copy of pE1077-23. Conclusions: This study showed the presence of two cointegrate formation events in the formation and spread of a poxtA/fexB -carrying plasmid in E. faecium . One was the integration of a transposon into a plasmid while the other was the integration of a TU into a different site of the same type of plasmid-borne transposon from which it originated. In both events, IS 1216E played a major role, suggesting that IS 1216E- mediated transposition and translocation processes aid the dissemination and persistence of important antimicrobial resistance genes, such as poxtA, among enterococci.